Lateral neck dissection for well‐differentiated thyroid carcinoma: A systematic review. (10th February 2014) - Madenci, Arin L.; Caragacianu, Diana; Boeckmann, Jacob O.; Stack, Brendan C.; Shin, Jennifer J.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Management of the lateral neck in well‐differentiated thyroid carcinoma (WDTC) remains a topic of ongoing debate. A systematic review was performed to determine if patients with WDTC who undergo lateral neck dissection (LND) have significantly different survival, recurrence, or procedure‐related complication rates, as compared to those who do not. Data Sources A computerized search of MEDLINE from 1966 to October 2012 was performed, supplemented with manual searches. Review Methods A priori criteria were used to evaluate 924 studies. Data extraction was performed by independent reviewers and focused on survival, recurrence, postoperative complications, study designs, and potential confounders. Results Forty‐seven criterion‐meeting studies included 24, 153 participants. Stage‐specific data were limited. The small volume of data specific to the N0 neck (n = 3 studies, 6.3%) demonstrates no difference in disease‐free survival (DFS) or recurrence with versus without LND. The data regarding the N+ neck (n = 14 studies, 29.2%) were mixed with regard to the impact of LND on DFS and recurrence. The preponderance of data was reported in analyses of mixed or unreported nodal status (n =31 studies, 64.6%). Among these studies, the majority reported no difference in overall survival, DFS, disease‐specific survival, or recurrence, but overall data were mixed and subject to confounding by indication and limitations in power. Conclusions Data regarding the impact of LND on survival, recurrence, and postoperative complications are mixed. Routine prophylactic LND for WDTC does not have a clearly advantageous risk‐to‐benefit ratio. Level of Evidence Laryngoscope, 124:1724–1734, 2014